WHO ENGAGES WITH AGRICULTURAL EXTENSION SERVICES? EVIDENCE FROM FARMING HOUSEHOLDS IN PAKISTAN (Contemporary Journal of Social Science Review, 2025)
Agricultural extension services are a key policy tool for improving farm productivity and rural livelihoods, yet their use remains limited in many developing countries. This study examines who engages with agricultural extension services in Pakistan using nationally representative data from the Pakistan Social and Living Standards Measurement Survey 2019–20. Focusing on farm households, the analysis applies a Linear Probability Model to identify socioeconomic, geographic, and farm-level factors associated with extension utilization. The results show that overall utilization is low, with fewer than 16 percent of farm households reporting any engagement. Extension use rises steadily with household wealth and is significantly higher among contract cultivators, while sharecroppers and livestock-only households remain largely excluded. Provincial differences are evident, and urban farm households are less likely to use extension services. Age reduces engagement slightly, while education plays a limited direct role. The findings highlight the need for more targeted and inclusive extension policies in Pakistan.